2019
DOI: 10.21041/ra.v10i1.421
|View full text |Cite
|
Sign up to set email alerts
|

Ações e efeitos deletérios do fogo em estruturas de concreto. Uma breve revisão

Abstract: Este artigo tem o objetivo de apresentar e discutir brevemente alguns tópicos essenciais sobre a ação do fogo nas estruturas de concreto e quais os eventuais efeitos deletérios das elevadas temperaturas no material concreto propriamente dito. Foi realizada uma revisão da literatura, abordando o comportamento do concreto (visto como um material e como um elemento estrutural) quando exposto às ações térmicas excepcionais e severas procedentes de um cenário de incêndio, contribuindo para desmistificar algumas cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…12,13 This type of spalling can lead to the failure of concrete layers, commonly reaching thicknesses between 25 and 100 mm, varying on each specific case. 14 Jansson 15 recounted that the works of Barret 16 in 1854 were the first time recorded observation of concrete spalling was made. The researched showed that when the aggregate used to manufacture concrete was flint, the concrete was said to have split and yielded when it was exposed to fire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 This type of spalling can lead to the failure of concrete layers, commonly reaching thicknesses between 25 and 100 mm, varying on each specific case. 14 Jansson 15 recounted that the works of Barret 16 in 1854 were the first time recorded observation of concrete spalling was made. The researched showed that when the aggregate used to manufacture concrete was flint, the concrete was said to have split and yielded when it was exposed to fire.…”
Section: Introductionmentioning
confidence: 99%
“…Explosive spalling of concrete can be best described as an extreme showering of heated sections of concrete that can affect firefighting service personnel, making their work significantly more challenging and hazardous 12,13 . This type of spalling can lead to the failure of concrete layers, commonly reaching thicknesses between 25 and 100 mm, varying on each specific case 14 . Jansson 15 recounted that the works of Barret 16 in 1854 were the first time recorded observation of concrete spalling was made.…”
Section: Introductionmentioning
confidence: 99%
“…The primary consequences of fire exposure on concrete include reduced compressive strength and spalling, characterized by the forceful expulsion of material from a structural member's surface [8,9]. Spalling can manifest in situations characterized by pronounced temperature gradients during heating and cooling phases [8,[10][11][12]. To study the spalling to the tunnel lining, different researchers conducted different experimental research and concluded the results.…”
Section: Introductionmentioning
confidence: 99%
“…Material parameters.As mentioned above, the thermo-hydral mechanism is mainly responsible for the effects of material parameters. Several studies have shown that (i) riverbed aggregates are more spalling prone than basalt and granite aggregates[32], (ii) calcareous aggregates spall more than silicocalcareous aggregates[35,36], (iii) lower w/c ratio increases spalling risk by making the concrete denser[32,[37][38][39], (iv) high strength concrete is more prone to spalling due to lower permeability[40][41][42], (v) higher moisture content allows more water availability inside concrete thereby accelerating spalling[33,35,38], and (vi) the age of concrete structures does not seem to have any apparent effect on concrete spalling characteristics[39,[43][44][45]. However, the effect of maximum aggregate size[46][47][48] and cement type[32,35,49] is still not evident from the conflicting results reported in the literature.…”
mentioning
confidence: 99%